(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Sustainable transport provision in a country with low population density, a relatively small population and relatively low numbers of tourists is significant for transition toward a greener, more inclusive, and cost-efficient transport system. Latvia's transport policy aligns with the European Green Deal, which aims to shift towards sustainable and smart mobility. While prime concerns are carbon dioxide (CO2) emissions and developing a multimodal public transport network with rail as its backbone and inclusive mobility, transport poverty has not been a priority. To ensure truly inclusive mobility in terms of transport poverty as well, a holistic approach is needed—one that unites social and environmental considerations into transport planning through targeted subsidies, expanded rural transport services and equality in less populated and remote areas, and investments in multimodal infrastructure. The aim of this study is to analyze the current state of sustainable people mobility in Latvia, focusing on the interaction between environmental goals and active transport, accessibility and social equity. Particularly focus on the problem of transport poverty, which is a key challenge for achieving inclusive mobility, especially for the most disadvantaged populations. This study uses the transport poverty indicators mentioned in the European Commission’s final report (2024) on transport poverty and data from various sources to identify the situation in Latvia and the European Union. Such a study has not been conducted before in Latvia. This study contributes to the growing discourse on sustainable mobility, highlighting the critical need to address transport poverty in the context of Latvia. Key findings include proposals for promoting active mobility and the transition to low-emission vehicle technologies, as well as how to make mobility more equitable. The results show that Latvia has made progress in reducing greenhouse gas emissions and implementing a public transport policy. Although obstacles such as uneven infrastructure development, the high cost of sustainable transport options and the lack of integration of urban and rural transport networks continue to perpetuate inequalities in mobility access.